Correspondências fonológicas e lexicais entre Karitiána (Arikém, Tupí) e Tupí-Guaraní - Dietrich, Wolf (2013)
This paper presents a lexical comparison of the Karitiána language of the Arikém family with reconstructed forms of Proto-Tupí and Proto-Tupí-Guaraní, as well as with single TupíGuaraní languages and Mawé, as a contribution to consolidate the Proto-Tupí hypothesis. This study also aims at contributing with new cognate sets involving Karitiána and the other families compared. The Karitiána data come in part from my own field work, and in part from Landin’s dictionnary